Risk-Return Analysis of the Biopharmaceutical Industry as Compared to Other Industries - Popa, Cedric; Holvoet, Karel; Van Montfort, Tessa; Groeneveld, Floris; Simoens, Steven (Frontiers in Pharmacology, 2018)
Background: Profits in the biopharmaceutical industry have been scrutinized in social debate. However, drawing conclusions based on industry profitability only is inappropriate as such an analysis does not account for risks faced by investors. This study aims to measure risks and returns in the biopharmaceutical industry and investigates whether risk-adjusted return on investment in the biopharmaceutical industry is higher than that in other industries. Methods: To enable appropriate comparison, we identified six benchmark industries with characteristics that match those of the biopharmaceutical industry: automotive manufacturing, commercial aircraft manufacturing, consumer electronics, packaged food manufacturing, telecom, and oil and gas. For those industries, we selected the top 25 companies per industry, covering 35–65% of industry revenues. Data on return measures (i.e., net profit margin, return on equity, total shareholder return) and risk measures (i.e., volatility of total shareholder return, beta) were derived from Bloomberg over the 2004–2016 period. The Sharpe ratio was calculated as a measure of risk-adjusted return on investment and compared between industries. Results: Net profit margins varied between 12.6 and 19.5% in the biopharmaceutical industry, and ranged from 2.6 to 8.4% in the benchmark industries. Return on equity for the biopharmaceutical industry was above the average for the other industries. Total shareholder returns for the biopharmaceutical industry amounted to 11.7%, ranking fifth across the seven industries. The biopharmaceutical industry ranked sixth among the seven industries regarding beta, and sixth in terms of volatility of total shareholder return. The median Sharpe value for the biopharmaceutical industry ranked fifth of seven industries. Conclusion: Over the 2004–2016 period, the biopharmaceutical industry did not attain risk-adjusted return on investment in excess of that in other industries and, thus, did not outperform these industries.